The Influence of Social Media and Environmental Factors on Academic Performance of Student Nurses in South-West Nigeria - Babatunde, Ezekiel Olusegun (European Scientific Journal, ESJ, 2017)
The growing popularity and consideration of social networking sites having the ability to enhance interaction, academic participation and performance among lecturers and students respectively underscored an investigation into the influence of social media and environmental factors on academic performance of student nurses in Southwest Nigeria. The study is a survey design that adopted correlational research type. The population comprised all Student Nurses in all the Nursing Schools in Southwest Nigeria. Six schools purposively selected and a sample of 300 students randomly selected participated in the study. Two instruments: Social Media and Environmental Factor Questionnaire (SMEFQ) r=0.85 and Student Nurses Achievement Test (SNAT), r=0.72 was used to collect data. Three research questions guided the study and data collected was analysed using descriptive and inferential statistics. Result revealed that the three predictor variables correlated with each other in predicting students’ academic achievement. It also showed that Facebook ß = (-.162), t(-1.436) = .155, p>.005 contributed most among the predictor variables while the two predictors (social media and environmental factors) could not predict students academic performance in Nursing (F(2,77) =1.214, P= 0.303). It is recommended that students be encouraged to use social media adequately for academic purposes while government improve school physical structures and provide conducive learning environment for academic excellence.